The Application of The Agile Method for Software Development in Directorate General of Taxes (Indonesia’s Tax Authority) - Putra, Wide (2017)
The purpose of this dissertation is to answer the research question, which is “How Could The Agile Method be Applied in Directorate General of Taxes (DGT) Software Development Project?” It is important to answer the question because the use of Software application is essential in DGT business process, and DGT develop most of the software application by itself. The high-quality software application is produced by the proper software development process, which agile is believed by many people as the right method to use in the software development. The literature reviews that are analyzed in this dissertation are project management theory, Traditional Project management, Agile Theory, Information system and also DGT’s software development regulation. The analysis also conducted by interviewing the DGT’s employees who are involved in software development project. Moreover, there are interesting conclusion emergence from the discussion. Besides the good conditions that are already applied in DGT software development such as; the existance of agile regulation as a guidance and a legal basis, and the application of parts of agile manifesto. There are also the ones that still need to be fixed in the DGT’s software development process, such as; the level of development team understanding of the agile concept, the beraucracy factor and the non-existence of suitable environment that obstruct the application of agile manifesto, the development practices that were not done according to the regulation, and also the things that are not covered by the regulation. Several recommendations are provided by this dissertation, the actions that DGT should do to adopt the agile method fully. That are; Provide the training for development team members, distribute the knowledge about the agile concept to the management from a low level to the highest level, apply every single step in the regulation. Accommodate the needs of better environment and facilities for development team member. Moreover, The regulation should accommodate more of agile methodologies to give more option to use in specific case of software development project.